Understanding stone tool-making skill acquisition: Experimental methods and evolutionary implications. Issue 133 (August 2019) - Pargeter, Justin; Khreisheh, Nada; Stout, Dietrich
Abstract: Despite its theoretical importance, the process of stone tool-making skill acquisition remains understudied and poorly understood. The challenges and costs of skill learning constitute an oft-neglected factor in the evaluation of alternative adaptive strategies and a potential source of bias in cultural transmission. Similarly, theory and data indicate that the most salient neural and cognitive demands of stone tool-making should occur during learning rather than expert performance. Unfortunately, the behavioral complexity and extensive learning requirements that make stone knapping skill acquisition an interesting object of study are the very features that make it so challenging to investigate experimentally. Here we present results from a multidisciplinary study of Late Acheulean handaxe-making skill acquisition involving twenty-six naïve participants and up to 90 hours training over several months, accompanied by a battery of psychometric, behavioral, and neuroimaging assessments. In this initial report, we derive a robust quantitative skill metric for the experimental handaxes using machine learning algorithms, reconstruct a group-level learning curve, and explore sources of individual variation in learning outcomes. Results identify particular cognitive targets of selection on the efficiency or reliability of tool-making skill acquisition, quantify learning costs, highlight the likely importance of social support, motivation, persistence, and self-control in knapping skill acquisition, and illustrate methods for reliably reconstructing ancient learning processes from archaeological evidence.